2012
DOI: 10.3892/ol.2012.718
|View full text |Cite
|
Sign up to set email alerts
|

Increased voltage-dependent K+ channel Kv1.3 and Kv1.5 expression correlates with leiomyosarcoma aggressiveness

Abstract: Abstract. Voltage-dependent K + channels (Kv) are involved in the proliferation and differentiation of mammalian cells, since Kv antagonists impair cell cycle progression. Although myofibers are terminally differentiated, some myoblasts may re-enter the cell cycle and proliferate. Since Kv1.3 and Kv1.5 expression is remodeled during tumorigenesis and is involved in smooth muscle proliferation, the purpose of this study was to analyze the expression of Kv1.3 and Kv1.5 in smooth muscle neoplasms. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…The data suggests that DNA methylation is responsible for the observed decrease of Kv1.3 gene expression [22]. A significantly reduced expression of the channels was also observed in kidney, bladder, pancreas, lung, brain (astrocytoma, oligodendroglioma, and glioblastoma), stomach and prostate cancer [8,18,[22][23][24]. In the case of prostate cancer, there is also an inverse correlation between the expression of the channels and the stage of the disease [23].…”
Section: Kv13 Channels In Cancer Diagnostics and Therapymentioning
confidence: 70%
See 2 more Smart Citations
“…The data suggests that DNA methylation is responsible for the observed decrease of Kv1.3 gene expression [22]. A significantly reduced expression of the channels was also observed in kidney, bladder, pancreas, lung, brain (astrocytoma, oligodendroglioma, and glioblastoma), stomach and prostate cancer [8,18,[22][23][24]. In the case of prostate cancer, there is also an inverse correlation between the expression of the channels and the stage of the disease [23].…”
Section: Kv13 Channels In Cancer Diagnostics and Therapymentioning
confidence: 70%
“…An increased expression of Kv1.3 channels was observed in the case of breast, colon, smooth muscle (leiomyosarcoma), skeletal muscle (alveolar rhabdomyosarcoma) and lymph node cancer [8,17] and in mature neoplastic B cells in chronic lymphocytic leukemia (B-CLL) [20]. A significantly increased expression of Kv1.3 channels that was positively correlated with tumor aggressiveness was recently observed in the case of leiomyosarcoma and alveolar rhabdomyosarcoma [8,18]. In the case of breast cancer, contradictory data has been obtained [17, 21, and 22].…”
Section: Kv13 Channels In Cancer Diagnostics and Therapymentioning
confidence: 93%
See 1 more Smart Citation
“…The latest probable explanation is that non-conducting mechanism contribute to proliferation rather than ion-flux mechanism [24]. Previous studies manifested for the first time that Kv1.3 and Kv1.5 are altered during smooth muscle carcinogenesis and showed that the increased expression of K1.3 and Kv1.5 prompt leiomyosarcoma aggressiveness [25]. Likewise, the result of previous study demonstrated that the specific knockdown of Kv9.3 decrease proliferation in human colon and lung carcinoma cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although Kv1.3 was first cloned from brain tissue, its expression is widely distributed throughout the body (Swanson et al, 1990; Bielanska et al, 2009, 2010). This channel is highly expressed in lymphocytes and the olfactory bulb (Stuhmer et al, 1989), and several studies have reported that it is also expressed in the hippocampus (Veh et al, 1995), epithelia (Grunnet et al, 2003), adipose tissue (Xu et al, 2004), and both skeletal, and smooth muscle (Villalonga et al, 2008; Bielanska et al, 2012a,b). …”
Section: Voltage-dependent K+ Channels Kv13 and Kv15mentioning
confidence: 99%